Pengaruh Kepemimpinan Kepala Sekolah, Akreditasi Sekolah dan Anggaran Pendidikan Sekolah terhadap Kinerja Guru SMA Negeri di Kabupaten Pidie Jaya - Zuhri, Zuhri; Fauzi, Fauzi; Bahri, Saiful (peusangan, 2023)
This research was conducted on a sample of 211 public high school teachers in Pidie Jaya district. With the aim of knowing: a) the partial influence of Principal Leadership, School Accreditation and School Education Budget factors on teacher performance, b) the simultaneous effect of Principal Leadership, School Accreditation and Education Budget factors on teacher performance. The data analysis technique uses parametric statistics with multiple regression analysis models. The research results show that; The results of processing and analysis of survey data show and prove the hypothesis of this study, namely: a) There is a partial significant effect on Principal Leadership, school accreditation and school budgets on the performance of public high school teachers in Pidie Jaya Regency. Where the accreditation factor gives the biggest contribution among the factors studied. B). Simultaneously, the principal's leadership, school accreditation, and school budget contributed 53.5% to the performance of public high school teachers in Pidie Jaya District.